Energy Harvesting Based on Living Plants For Smart Farming - Tuangrat Pechsiri; Supachai Puengsungwan (ASEAN Journal of Science and Engineering, 2023)
This paper presents the bio-generator method for smart farming. Energy harvesting (EH) from the natural environment is becoming widely introduced as a sustainable energy source. Nowadays, smart devices for IoT are critically needed to have an EH type of power supply for continuity of sensing changes. The EH presented in this paper consists of two parts: 1) EH as a supply for sensor nodes for WSNs 2) EH as a sensing module for monitoring soil conditions. The principle of EH is based on the PMFC principle. To evaluate the proposed idea, experiments with avocado trees under different conditions were performed. The harvestable voltage ranges from 0.37 to 0.65 Volts, and the voltage can be converted up to 3.12 Volts using a BQ25504 boost converter. The output voltage of the boost converter is sufficient to supply a sensor node in WSN applications.